The value of terroir: A historical analysis of Bordeaux and Champagne, the world's first geographical indications - Catherine Haeck; Giulia Meloni; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2018)
Previous studies on the value of terroir, or more generally geographical indications (GI), used hedonic techniques. We use historical data and exploit temporal and geographical variations in the introduction of wine GIs in early twentieth century France to study the impact on the price of specific wines in the years and decades following their introduction. We find large effects of GIs on prices of some Champagne wines, but no significant impact on Bordeaux or other Champagne wines.
Keywords: C21; L51; L66; N53; Q11; Q18; 330; Treatment effects; Appellations; European agriculture; regulation; wine history